Category management operating model design and implementation : Study of case company Valmet Automotive - Ääritalo, Susanna (My University, 2021)
The current challenging situation in the manufacturing industry is forcing companies to further strengthen operations and streamline processes. There are changes in the industry in terms of current corona crisis at the time when writing this thesis, but also supply chain risk management, electrification and sustainable business are critical topics for automotive industry. To respond to this, category management benefits internal stakeholders, customers and suppliers. The aim of the study was to create a functional category management model for the target company, as well as provide the tools for implementing category management and ensuring continuous process development efficiently and profitably. The tools also help the company to build category strategies for each category effectively. The client of this study is the Finnish automotive manufacturing company, Valmet Automotive Oy. The theoretical part of the study is based on the knowledge of experts and the literature. However, the main focus of the study is in the professional literature, as the target company has not previously used a category management model. In addition to theory, the requirement for developing the system was to identify the company’s culture behind the need of process re-engineering. On the basis of the experiments, it was possible to deepen the problem itself, as well as to identify potential areas for development for which the company is seeking a solution. Cooperation and the flow of information are clearly the most important measures for the functioning supply chain strategy. As a result, the category management model shall have the right performance metrics to effectively monitor the functionality of the process. The study succeeded in finding out a suitable category management operating model through process reform for the client company. Through the study, the required system was developed including the A3 model developed by Toyota, the matrix organization model, and the spend analysis created on the PowerBI platform which were identified as the most suitable tools for the target company.

Valmistusteollisuuden tämän hetken haastava tilanne asettaa yritykset entistä pakotetummin tehostamaan toimintaa sekä virtaviivaistamaan prosesseja. Autoteollisuudessa muutoksia on tutkimuksen kirjoitushetkellä käynnissä olevan koronapandemian lisäksi niin toimitusketjujohtamisen riskien hallinnassa, sähköistymisessä sekä kestävän kehityksen adaptoinnissa. Vastatakseen tähän, kategoriajohtamisen kautta saadaan hyötyä niin sisäisille sidosryhmille, kuin asiakkaille ja toimittajille. Lopputyön tavoitteena oli luoda kohdeyritykselle toimiva kategoriajohtamismalli, sekä työkalut kategoriajohtamisen implementointiin ja jatkuvan prosessikehityksen varmistamiseen tehokkaasti sekä kannattavasti. Työkalut auttavat yritystä myös rakentamaan yksityiskohtaiset kategoriastrategiat jokaiselle kategorialle toimivasti. Työn toimeksiantajana on suomalainen valmistavan autoteollisuuden yritys Valmet Automotive Oy. Työn teoriaosuus pohjautuu asiantuntijoiden osaamiseen, sekä kirjallisuuteen. Tutkimuksen pääpaino pysyi kuitenkin ammattikirjallisuudessa, sillä kohdeyrityksessä ei ole ennen käytetty kategoriajohtamismallia. Järjestelmän kehittämisen vaatimuksena oli teorian lisäksi yrityksen kulttuurin tunnistaminen prosessin uudelleensuunnittelun tarpeen taustalle. Kokemusten pohjalta saatiin paneuduttua syvällisemmin itse ongelmaan, sekä tunnistettua potentiaaliset kehityskohteet, joihin yritys hakee ratkaisua. Koko toimitusketjun toimivuuden kannalta yhteistyö ja tiedon kulku ovat selkeästi tärkeimpiä toimenpiteitä. Tämän myötä kategoriajohtamismallilla tulee olla oikeat suorituskykymittarit, joiden avulla voidaan tehokkaasti seurata prosessin toimivuutta. Tutkimus onnistui identifioimaan kohdeyritykselle toimivan toimintamallin ja sitä kautta prosessiuudistuksen. Tutkimuksen kautta kehitettiin vaadittava systeemi sisältäen kohdeyritykselle toimiviksi määritellyt työkalut, kuten Toyotan kehittämän A3-mallin, matriisiorganisaatiomallin, sekä kuluanalyysin työstettynä PowerBI-alustalle.
Keywords: category management; corporate strategies; processes; supply chains; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management